B.W. Huebsch papers - Huebsch, B. W. (Benjamin W.), 1876-1964.; Franko, Sam, 1857-1937
Chiefly correspondence relating to Huebsch's career as a publisher under his own imprint, B.W. Huebsch, from 1900 to 1924, and after its merger with Viking Press in 1924, at that publishing house until 1964. Reflects his thoughts on literature and his work for liberal causes in many fields. Also documents his publication of the liberal weekly, Freeman, and activities with organizations including the American Civil Liberties Union and the National Association of Book Publishers. Includes diary entries, speeches, articles, and other papers; notebooks containing advertisements for the B.W. Huebsch publishing house; literary manuscripts of Franz Werfel, Stefan Zweig, and others; and an autograph collection of musical personalities belonging to Sam Franko. Correspondents include Sherwood Anderson, Van Wyck Brooks, Theodore Dreiser, Irwin Edman, Lion Feuchtwanger, Sam Franko, Rumer Godden, Daniel A. Huebsch, Harold Joseph Laski, D.H. Lawrence, William Ellery Leonard, Roger Martin du Gard, Francis Neilson, Albert Jay Nock, Walter Pach, Bertrand Russell, Siegfried Sassoon, Upton Sinclair, Sylvia Townsend Warner, Franz Werfel, Patrick White, and Stefan Zweig.
Publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Sherwood, -- 1876-1941 -- Correspondence; Brooks, Van Wyck, -- 1886-1963 -- Correspondence; Dreiser, Theodore, -- 1871-1945 -- Correspondence; Edman, Irwin, -- 1896-1954 -- Correspondence; Feuchtwanger, Lion, -- 1884-1958 -- Correspondence; Franko, Sam, -- 1857-1937 -- Correspondence; Godden, Rumer, -- 1907-1998 -- Correspondence; Huebsch, Daniel A. -- 1871- -- Correspondence; Laski, Harold Joseph, -- 1893-1950 -- Correspondence; Lawrence, D. H. -- 1885-1930 -- Correspondence; Leonard, William Ellery, -- 1876-1944 -- Correspondence; Martin Du Gard, Roger, -- 1881-1958 -- Correspondence; Neilson, Francis, -- 1867- -- Correspondence; Nock, Albert Jay, -- 1872 or 1873-1945 -- Correspondence; Pach, Walter, -- 1883-1958 -- Correspondence; Russell, Bertrand, -- 1872-1970 -- Correspondence; Sassoon, Siegfried, -- 1886-1967 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Warner, Sylvia Townsend, -- 1893-1978 -- Correspondence; Werfel, Franz, -- 1890-1945.; Werfel, Franz, -- 1890-1945 -- Correspondence; White, Patrick, -- 1912-1990 -- Correspondence; Zweig, Stefan, -- 1881-1942.; Zweig, Stefan, -- 1881-1942 -- Correspondence; American Civil Liberties Union; B.W. Huebsch (Firm); National Association of Book Publishers; Viking Press; Freeman (New York, N.Y. : 1920); Authors and publishers; Autographs -- Collections; Liberalism -- United States; Literature; Musicians -- Autographs; Political science -- Periodicals; Publishers and publishing -- Societies, etc; Publishers and publishing -- United States; Publishers